2020
DOI: 10.1002/admt.202000115
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Grown Monolithic Au/TiO2 Catalysts on Flexible Ti Mesh for Efficient Low‐Temperature CO Oxidation

Abstract: The development of advanced catalyst integration strategy is of great importance and promising for long‐term and stable gas catalysis in environmental processing. However, conventional catalyst fabrication techniques including spray method and spin coating cannot overcome the key problems of catalyst peeling off from substrate and related severe performance degradation. In this work, an in situ integration strategy of monolithic Au/TiO2 catalysts on Ti mesh for efficient and stable low‐temperature CO oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The typical synthetic procedures of the H 2 Ti 2 O 5 /Ti support involved a series of reaction steps, which included PEO, hydrothermal reaction, and ion exchange, which were systemically reported in our previous works. Mn and Cu active species were loaded onto the H 2 Ti 2 O 5 /Ti supports by using a simple coprecipitation method. A solution containing 30 mmol of Mn­(NO 3 ) 2 and Cu­(NO 3 ) 2 in 50 mL of ultrapure H 2 O was prepared, followed by the addition of 50 mL of a 30 mmol/L NaHCO 3 solution as the precipitating agent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical synthetic procedures of the H 2 Ti 2 O 5 /Ti support involved a series of reaction steps, which included PEO, hydrothermal reaction, and ion exchange, which were systemically reported in our previous works. Mn and Cu active species were loaded onto the H 2 Ti 2 O 5 /Ti supports by using a simple coprecipitation method. A solution containing 30 mmol of Mn­(NO 3 ) 2 and Cu­(NO 3 ) 2 in 50 mL of ultrapure H 2 O was prepared, followed by the addition of 50 mL of a 30 mmol/L NaHCO 3 solution as the precipitating agent.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we propose a synthetic strategy of monolithic catalysts, including plasma electrolytic oxidation (PEO), hydrothermal, and coprecipitation methods, to address the above issues. First, TiO 2 nanosheet arrays with robust substrate adhesion and a large surface area were in situ-prepared on flexible Ti mesh, as reported in our previous works. Then, highly dispersed Cu–Mn active components with excellent synergistic effects were loaded in situ onto the surface of TiO 2 supports to promote catalytic activity and durability. It has been demonstrated that the flexible Ti mesh-supported MnO x –CuO x /TiO 2 nanosheet monolithic catalysts could realize high NO x conversion and N 2 selectivity in the wide operating temperature range of 145–300 °C with excellent resistance to H 2 O and good recoverability after SO 2 poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, the electrolyte solution temperature is controlled below 25 °C by the cooling system to maintain the good oxidation quality of porous TiO 2 film. Detailed PEO process of Ti anode can be found in our previous works [15][16][17]. To synthesize Cu-Mn-O catalysts, the Ti mesh covered with rough TiO 2 film is inserted into an autoclave filled with mixed solution of Cu(NO 3 ) 2 , KMnO 4 and urea with a total concentration of 0.06 M in 40 ml and a molar ratio of Cu: Mn = 0:1, 2:1, 1:2 and 1:0, and the hydrothermal reaction to synthesize Cu-Mn-O catalysts is carried out at 150 °C for 6, 12 and 18 h to investigate any possible morphology evolution.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…This method has been applied to fabricate many 2D metal oxides/sulfides for PEC water splitting, such as Zn 1− x Cd x S [ 52 ] and TiO 2 . [ 53–56 ]…”
Section: D Semiconductor Photoanode In Pec Water Splittingmentioning
confidence: 99%